2015
DOI: 10.1128/jb.02401-14
|View full text |Cite
|
Sign up to set email alerts
|

SepD/SepL-Dependent Secretion Signals of the Type III Secretion System Translocator Proteins in Enteropathogenic Escherichia coli

Abstract: The type III protein secretion system (T3SS) encoded by the locus of enterocyte effacement (LEE) is essential for the pathogenesis of attaching/effacing bacterial pathogens, including enteropathogenic Escherichia coli (EPEC), enterohemorrhagic E. coli (EHEC), and Citrobacter rodentium. These pathogens use the T3SS to sequentially secrete three categories of proteins: the T3SS needle and inner rod protein components; the EspA, EspB, and EspD translocators; and many LEE-and non-LEE-encoded effectors. SepD and Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…To identify them, we generated whole and partial (i.e., encoding the large cytoplasmic domains of escV and escU) chromosomal gene deletions. None of the derivative strains secreted EspA in vivo ( Fig 3B; Appendix Fig S1A), in agreement with previous results (Dziva et al, 2004;O'Connell et al, 2004;Nadler et al, 2006;Deng et al, 2015), nor formed actin pedestals on HeLa cells (Appendix Fig S1D-L), an assay reporting effector injection (e.g., Tir) via the EspA filaments and the EspB/D translocon pore (Creasey et al, 2003).…”
Section: Cesab/espa Targeting To the Injectisome Requires Sepl And Escvsupporting
confidence: 91%
See 1 more Smart Citation
“…To identify them, we generated whole and partial (i.e., encoding the large cytoplasmic domains of escV and escU) chromosomal gene deletions. None of the derivative strains secreted EspA in vivo ( Fig 3B; Appendix Fig S1A), in agreement with previous results (Dziva et al, 2004;O'Connell et al, 2004;Nadler et al, 2006;Deng et al, 2015), nor formed actin pedestals on HeLa cells (Appendix Fig S1D-L), an assay reporting effector injection (e.g., Tir) via the EspA filaments and the EspB/D translocon pore (Creasey et al, 2003).…”
Section: Cesab/espa Targeting To the Injectisome Requires Sepl And Escvsupporting
confidence: 91%
“…We anticipate that the novel receptor role revealed here and analyzed in detail for CesAB might be universal for translocator chaperones, even those structurally distinct from CesAB [e.g., the CesD and CesD2 class III chaperones of EspB and D (Wainwright & Kaper, ; Neves et al , )]. This would be in agreement with, structures of gatekeepers co‐complexed with chaperone homologues (Archuleta & Spiller, ), pull‐down assays (Kubori & Galan, ; Silva‐Herzog et al , ), and the abolished secretion of all translocators in SepL, SepD, and CesL mutants (Fig EV5H; Wang et al , ; Younis et al , ; Deng et al , ). In this capacity, SepL may act indeed as an early pseudo‐effector (Younis et al , ), that occupies EscV, switches it to preferentially accepting translocators and blocks binding of all other effectors.…”
Section: Discussionsupporting
confidence: 80%
“…The chimeric proteins were expressed in WT EPEC (normal secretion), the Δ escN mutant (no secretion), and the Δ sepD and Δ sepL mutants (hypersecretion of effectors). Because many T3SS proteins containing a secretion signal exhibit significantly higher secretion in the Δ sepD and Δ sepL mutant strains (37, 49), we used these strains to enable the detection of low levels of secreted substrates.…”
Section: Resultsmentioning
confidence: 99%
“…SepL is a known member of the gatekeeper family of proteins, which includes YopN in Yersinia , InvE and SsaL in Salmonella , and MxiC in Shigella (7). SepD, on the other hand, is not well conserved in other pathogens, and as such, it has a single, functional homolog, SpiC, which was identified in Salmonella pathogenicity island 2 (3638). In addition, the YscB protein was suggested to belong to the SepD family of proteins because of its analogous position within the Yersinia pathogenicity island (39).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the secretion and translocation signal in the N-terminal 20 amino acids of translocon proteins from enteropathogenic E. coli is not sufficient to mediate translocon-specific secretion in mutant strains which lack the control proteins SepD and SepL (74)(75)(76)(77)(78). Therefore, it was suggested that T3S is controlled by composite signals, which are involved in a multistep recognition process (68,74,75). Notably, however, this model does not appear to apply to HrpB2, suggesting that the presence of additive export signals in T3S substrates is not a general rule.…”
Section: Discussionmentioning
confidence: 99%